2008
DOI: 10.1164/rccm.200706-870oc
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Augments Myeloid Dendritic Cell Influx into the Airways in Patients with Allergic Asthma

Abstract: Rationale: Epidemiologic studies have shown that exacerbation of asthma is modulated by environmental endotoxin. High levels of endotoxin are associated with asthma symptoms and the current use of asthma medication. However, the underlying mechanisms by which endotoxin modulates asthma are not completely understood. Objectives: The aim of the study was to test whether endotoxin enhances the response of individuals with allergic asthma to allergen, and to determine if this interaction is associated with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 46 publications
7
44
0
Order By: Relevance
“…The crucial task of mDCs is the continuous surveillance of antigen-exposed sites throughout the body and the initiation of primary T-cell responses including T-cell polarization into Th1 and Th2 cells by secreting cytokines and expressing costimulatory molecules after activation (17,29). DCs, particular in mDCs, have a specific and important role in pathogenesis of human asthma (11)(12)(13). Recently, PGI 2 is regarded as a potential treatment of asthma by their antiinflammatory effect in vitro (14,30) and in animal model (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial task of mDCs is the continuous surveillance of antigen-exposed sites throughout the body and the initiation of primary T-cell responses including T-cell polarization into Th1 and Th2 cells by secreting cytokines and expressing costimulatory molecules after activation (17,29). DCs, particular in mDCs, have a specific and important role in pathogenesis of human asthma (11)(12)(13). Recently, PGI 2 is regarded as a potential treatment of asthma by their antiinflammatory effect in vitro (14,30) and in animal model (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a murine asthma model, myeloid dendritic cells (mDCs) accumulate in the allergen-challenged airways during the acute phase, and the depletion of mDCs attenuates the airway inflammation and hyperresponsiveness (10). In human asthma, mDCs accumulate in bronchoalveolar lavage fluid after an allergen challenge (11), and the influx of mDCs into the airways can be augmented by endotoxins (12). The induction and maintenance of inflammatory responses to allergens in persistent airway disease needs the involvement of mDCs (13).…”
Section: Introductionmentioning
confidence: 99%
“…Like neutrophils, lung macrophages are crucial in host defense against infections and have long been recognized as undergoing activation in asthma (29). Recently, Schaumann et al (30) have shown that LPS increases influx of macrophage-like cells into alveolar space and enhances allergic inflammation in the lung of asthmatics. Indeed, macrophage activation is tightly regulated by TLRs and IFN-␥, and these molecules have been shown to increase the production of proinflammatory cytokines (e.g., macrophage inflammatory protein 1␣, GM-CSF, and IL-12) and to activate transcriptional programs (e.g., NF-B and ERK1/2 MAPK) (31) in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of mononuclear phagocytes into asthmatic airways is well documented (16,17), as is strong evidence for cross-talk between these cells and epithelial cells in asthma (15,31). Therefore, we first evaluated the role of mononuclear phagocytes in responding to HDM in our system.…”
Section: Hdm Induces Cytokine Production and Ikbz Expression In Monocmentioning
confidence: 99%
“…There is also evidence of cross-talk between epithelial cells and dendritic cells that enhances the allergic response in asthma (15). Exposure to allergic antigens is associated with increased influx of monocytes, which differentiate into macrophages and dendritic cells in the airway mucosa of both mice and humans (16)(17)(18). Thus, understanding the molecular mechanisms that regulate the innate immune response involved in house dust mite-induced asthma is fundamental to the development of new therapeutics.…”
mentioning
confidence: 99%